Achievements Coaching at the Sekewet Futsal Family Club - Rendy Husaini Gumay; Rury Rizhardi; Endie Riyoko; Husni Fahritsani (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. This research aims to thoroughly examine the progress of achievements within the Sekewet Futsal Family Club. Comprehensive coaching is essential, encompassing various aspects such as club management, accomplishments, facilities, infrastructure, and financial resources. The effectiveness of these elements significantly influences the club's overall success and achievements. Materials and methods. This study employs descriptive qualitative research. Qualitative data is a research approach based on positivistic (concrete data), research data in the form of numbers that will be measured using statistics as a calculation test tool, related to the problem being studied to produce a conclusion. The data collection methods utilized in this study included observation, documentation, and interviews. Observation and interviews were the chosen data collection tools to gather primary data for this research, while documentation in the form of existing archives provided supporting and secondary data. Results. The analysis of the interviews indicates that the club management is currently in the process of formulating comprehensive performance indicators. This initiative is aimed at fostering continual improvement within the club's operations. Furthermore, the coach is dedicated to refining performance metrics to ignite and sustain the athletes' passion and determination, ultimately propelling them towards achieving their full potential. Conclusion. Coaching should be consistently and effectively implemented to encompass a wide range of essential components. These include but are not limited to talent identification and development, strategic staff recruitment and management, efficient facility and infrastructure oversight, meticulous program organization, and comprehensive performance evaluation.